2006
DOI: 10.1016/j.juro.2006.07.054
|View full text |Cite
|
Sign up to set email alerts
|

Citrate Concentrations in Human Seminal Fluid and Expressed Prostatic Fluid Determined via 1 H Nuclear Magnetic Resonance Spectroscopy Outperform Prostate Specific Antigen in Prostate Cancer Detection

Abstract: In vitro nuclear magnetic resonance spectroscopic measurement of the citrate concentration in semen or expressed prostatic secretions outperforms prostate specific antigen testing for detecting prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 16 publications
5
83
0
1
Order By: Relevance
“…Recently, by mutational analysis of the SLC25A1 gene (Edvardson et al, 2013;Nota et al, 2013), different mutations were identified in patients with agenesis of corpus callosum and hydroxyglutaric aciduria. Furthermore, direct measurements by liquid chromatography-tandem mass spectrometry (van de Wier et al, 2013) and nuclear magnetic resonance-based methods (Hricak, 2005;Kline et al, 2006) highlighted altered citrate levels in non-alcoholic fatty liver disease (NAFLD) and prostate cancer, respectively. Finally, the use of citrate as a therapeutic drug was also tentatively tested (Zhang et al, 2009).…”
Section: The Multifunctional Role Of Citratementioning
confidence: 99%
“…Recently, by mutational analysis of the SLC25A1 gene (Edvardson et al, 2013;Nota et al, 2013), different mutations were identified in patients with agenesis of corpus callosum and hydroxyglutaric aciduria. Furthermore, direct measurements by liquid chromatography-tandem mass spectrometry (van de Wier et al, 2013) and nuclear magnetic resonance-based methods (Hricak, 2005;Kline et al, 2006) highlighted altered citrate levels in non-alcoholic fatty liver disease (NAFLD) and prostate cancer, respectively. Finally, the use of citrate as a therapeutic drug was also tentatively tested (Zhang et al, 2009).…”
Section: The Multifunctional Role Of Citratementioning
confidence: 99%
“…Our long history of applications of NMR to prostate cancer diagnosis 2,25,26,[33][34][35][36][37] suggested that we turn to this area for a candidate cell-surface epitope to discriminate between cancer cells and normal, non-malignant cells. Research on prostate cancer-specific cell markers 25,[27][28][29] led to the identification of PSMA, the folate receptor, as a cell-surface protein that is highly-overexpressed on prostate tumors.…”
Section: Specific Binding Of Anti-psma-conjugated Spions To Psma-posimentioning
confidence: 99%
“…In the testes, NaCT is expressed in sperm cells (P. M. Martin and V. Ganapathy, unpublished data). Because seminal fluid contains high concentrations of citrate (∼130 mM) (Kline et al, 2006), we speculate that NaCT in spermatozoa mediates the concentrative uptake of citrate from seminal fluid into sperm cells to dx.doi.org/10.1124/jpet.114.221523. s This article has supplemental material available at jpet.aspetjournals.org. serve as a metabolic fuel.…”
Section: Introductionmentioning
confidence: 99%